Non-Ionic Surfactants Antagonize Toxicity of Potential Phenolic Endocrine-Disrupting Chemicals, Including Triclosan in Caenorhabditis elegans - Alfhili, Mohammad A. (Mol Cells, 2018)
Triclosan (TCS) is a phenolic antimicrobial chemical used in consumer products and medical devices. Evidence from in vitro and in vivo animal studies has linked TCS to numerous health problems, including allergic, cardiovascular, and neurodegenerative disease. Using Caenorhabditis elegans as a model system, we here show that short-term TCS treatment (LC(50): ~0.2 mM) significantly induced mortality in a dose-dependent manner. Notably, TCS-induced mortality was dramatically suppressed by co-treatment with non-ionic surfactants (NISs: e.g., Tween 20, Tween 80, NP-40, and Triton X-100), but not with anionic surfactants (e.g., sodium dodecyl sulfate). To identify the range of compounds susceptible to NIS inhibition, other structurally related chemical compounds were also examined. Of the compounds tested, only the toxicity of phenolic compounds (bisphenol A and benzyl 4-hydroxybenzoic acid) was significantly abrogated by NISs. Mechanistic analyses using TCS revealed that NISs appear to interfere with TCS-mediated mortality by micellar solubilization. Once internalized, the TCS-micelle complex is inefficiently exported in worms lacking PMP-3 (encoding an ATP-binding cassette (ABC) transporter) transmembrane protein, resulting in overt toxicity. Since many EDCs and surfactants are extensively used in commercial products, findings from this study provide valuable insights to devise safer pharmaceutical and nutritional preparations.